Fundamental Ethics In Islamic Political Thought - Muhammad Rizky HK (UIN Mataram, 2021)
This article attemps to explore the concept of shura and its possibility to be an ethical foundation of Islamic Political Thought. In order to discuss this issue, the main focus will be directed on two main discussion; The ground concepts of Islamic Political Thought, and The Islamic concepts: shura (consultation) It is already known that shura concepts has been widely interpreted as a theoretical basis for electoral democracy in Islam. The main purpose is to present a more philosopical view of Islamic political thought throught it ethical basis and to show that is possible to enrich the discourse on Islamic political though with ethical concept within Islamic dogma